Custom MPPT design of solar power switching network for racing car - Uddin, Md. Nasir; Rashid, Muhammad Mahbubur; Rahman, Muhammad Towhidur; Hossain, Belayet; Salam, S M; Nithe, N A (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper approach to design and build a highly efficient solar-powered race car for Solar Jackets Racing Team, will focus on developing a system to charge the car batteries given the energy received from solar panels throughout the day. It will utilize a switching power supply circuit to handle the variable amount of input power. The circuit will include an inductor, a switch, and a diode to transfer the appropriate energy from the source (solar cells) to the load (car battery). The switch will be controlled by a microcontroller that employs maximum power point tracking (MPPT) technology to determine how much current and voltage should be sent to the batteries to produce maximum power.